Enantioselective synthesis of guggultetrol and D-ribo-phytosphingosine tetraacetate via L-proline catalyzed sequential alpha-aminooxylation/Horner-Wardsworth-Emmons olefination-Sharpless asymmetric dihydroxylation strategy - Venkataramasubramanian, V.; Kumar, B. Senthil; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2015)
An efficient enantioselective synthesis of two bioactive molecules, that is, guggultetrol and D-ribo-phytosphingosine, is described with high enantioselectivity (>98% ee) starting from commercially available 1-hexadecanol. The synthesis comprises organocatalyzed sequential alpha-aminooxylation of an aldehyde followed by Horner-Wardsworth-Emmons olefination and Sharp less asymmetric dihydroxylation as the key chiral inducing steps. For both syntheses, gamma-hydroxy-alpha,beta-unsaturated ester serves as the common intermediate obtained from proline catalysis. (C) 2015 Elsevier Ltd. All rights reserved.